2018
DOI: 10.1371/journal.pone.0204081
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of extracellular polymeric substances from endodontic biofilms

Abstract: Apical periodontitis is frequently associated with the presence of bacteria biofilm, which has an indisputable impact on the prognosis of endodontic therapy due to the high resistance to adverse environmental conditions, chemicals, and antibiotic therapy that characterize bacteria within biofilm. The biofilm matrix acts as a protective shield over the encased microorganisms. The aim of this investigation was to identify the main biochemical components of biofilm matrix from endodontic mono- and dual-species bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In a previous research, we found that biochemical composition among these biofilms species varies significantly from monospecies to dual species [38]. A major fraction of polysaccharides, proteins, and fatty acids was identified in the monospecies biofilms compared to those in the dual-species biofilms [38]. ese results indicate that the two species influence each other at the biochemical level, and further data support the synergistic action between these two endodontic pathogens [39].…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In a previous research, we found that biochemical composition among these biofilms species varies significantly from monospecies to dual species [38]. A major fraction of polysaccharides, proteins, and fatty acids was identified in the monospecies biofilms compared to those in the dual-species biofilms [38]. ese results indicate that the two species influence each other at the biochemical level, and further data support the synergistic action between these two endodontic pathogens [39].…”
Section: Resultssupporting
confidence: 61%
“…In a previous research, we found that biochemical composition among these biofilms species varies significantly from monospecies to dual species [38]. A major fraction of polysaccharides, proteins, and fatty acids was identified in the monospecies biofilms compared to those in the dual-species biofilms [38].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Biofilms are multi-layered, localized, organized and heterogenous networks of microorganisms surrounded by self-produced extracellular polymeric substances (EPS) containing biomolecules such as polysaccharides, proteins, nucleic acids, and lipids [ 1 , 2 ]. Biofilms cause 80% of human bacterial infections, including biomaterial-associated infections, lung infections in cystic fibrosis patients and wound infections [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…New applications and markets for these molecules, including extracellular polymer-based bioproducts, are expected [34].Biofilm recovery is the first step toward characterizing the specific metabolites. Subsequently, depending on whether the analysis targets a particular component or not, the samples can be homogenized, fractionated into separate cells and soluble components, usually via centrifugation, and/or submitted to extraction in aqueous or nonaqueous solvents [35][36][37][38][39]. Enzymatic digestion can also be applied to recover a targeted component [35,36].In this study, we were interested in the biofilms formed by two Vibrio species known to produce exopolysaccharides in bioreactors.…”
mentioning
confidence: 99%